Utilizing Canva Application in Enhancing Students’ Speaking Skill in English: English - Ersika puspita Dani; Angel Agustin; Eliza Deani (Prodi Tadris Bahasa Inggris, 2023)
This research aimed to find out the effectiveness of using Canva Application in enhancing students’ speaking skill. Researchers used a quantitative method which is pre-experimental research design by applying pre-test and post-test based on the indicators of speaking skill, namely: pronunciation, vocabulary, fluency, and comprehension. There were 2 results found, 1) very good level (46.43%) was the most dominant in speaking skill, and fair level (7.14%) was the least of speaking skill by using Canva Application. 2) There were a differentiate between the result of students’ achievement in pre-test and post-test. Therefore, Canva Application is new and effective application in digital learning especially in enhancing students’ speaking skill.